Using stigmergy to co-ordinate pervasive computing environments. - Cahill, Vinny; Barron, Peter (IEEE Computer Society, 2004)
Pervasive computing environments have proven difficult to develop in a form that supports the integration and organisation of devices and applications in a spontaneous and transparent manner. This is partly due to the highly dynamic and unpredictable nature of these types of environments, and is often further hampered by the limited resources found on devices. In this paper we present a highly decentralized method of organising the components of a pervasive computing environment, supporting spontaneous interaction between entities and providing robust systemwide behavior. Our inspiration for this work stems from nature and the observations made by the French biologist Grasse on how social insects co-ordinate their actions using indirect communication via the environment, a phenomenon that has become known as stigmergy. In the stigmergic approach there are fewer dependences between entities allowing for the incremental construction and improvement of solutions without adversely effecting the rest of the pervasive computing environment. The approach is encapsulated in Cocoa, a framework that supports the use of stigmergy to build self-organising environments that promotes the autonomy of entities. Experience using Cocoa has shown that entities can be integrated into a pervasive computing environment in a spontaneous manner and that co-ordinated behavior can emerge.
Proceedings of 6th IEEE Workshop on Mobile Computing Systems and Applications (WMCSA 2004)
6th IEEE Workshop on Mobile Computing Systems and Applications (WMCSA 2004)
PUBLISHED
Keywords: Computer Science